Groβe Summe – groβes Problem? Warum die Debatte um die Target-Salden so hitzig ist - Adalbert Winkler (Wirtschaftsdienst, 2018)
1000 Mrd. Euro sind eine große Summe. Es ist daher verständlich, dass ein deutscher Target- Saldo in dieser Größe mediale Aufmerksamkeit erhält. Aber zeigt die große Summe auch ein großes Problem an? Hier gehen die Meinungen weit auseinander. Manche sprechen von Hysteriea und einem 'Scheinriesen'b, andere von 'echten Risiken für Deutschland'c, die in irreführender Weise verharmlost werden. Dieser Beitrag erläutert, warum die Target-Debatte so kontrovers und hitzig verläuft. – – The rise of the Bundesbank's target balance to about one billion euro has revived the debate among German economists about the interpretation and the risks associated with these balances for the German taxpayer and Germany as a whole. This paper explains why this debate is so heated by revealing that the opponents have sharply different views a) about the riskiness of assets purchased by the ECB when acting as a lender of last resort and by engaging in quantitative easing and b) about the risks for the German taxpayer and the economy if the ECB had not engaged in these activities.
Keywords: E44; E52; E 58; 330